Features of the dynamics of difficulty of competitive routines and the results of performances of the strongest teams in the world in artistic swimming - Anastasiya Petrenko; Larуsa Taran (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the dynamics of the development of the complexity of the competitive routines of the world's strongest teams in artistic swimming. Material and methods: theoretical analysis and generalization of scientific and methodological literature data, analysis of competition results, survey, methods of mathematical statistics. The results of performances and competitive routines of the five best performances of the World Championships (2015, 2017, 2019) and the Olympic Games (2008, 2012 and 2021) are analyzed. Results: comparing the World Championships 2015, 2017, 2019 and the Olympic Games 2008, 2012 and 2021, you can see that every year the athletes of the Ukrainian national team (from 27,7% to 42,5%, that is, by 14,8%) and Italian national team (from 29,4% to 38,3%, that is, by 8,8%) performances grew rapidly, relying on the time that athletes used to demonstrate the figure and elements hybrids. No less important are the data we obtained when comparing the time spent on acrobatic movements in the best countries of the world in artistic swimming. The data obtained allow us to state with confidence that acrobatic exercises play a very important role in artistic swimming. So we can see that from 2008 to 2015 years, the top teams performed a different number of acrobatic exercises and different types of acrobatic exercises, which differ in structure, but since 2017, the top countries began to perform almost the same number of acrobatic exercises from 5 to 6. This enables us to compare the demonstrated times with each other. Conclusions: the results obtained allow us to state the fact that with the same number of acrobatic exercises, the teams who performed less time (but same number) to demonstrate acrobatic exercises perform them faster than others, since the speed of «set-up and recovery time» (gathering and ungathering of the construction) of an acrobatic movement is also assessed in artistic swimming and is considered by «Execution» and «Difficulty» judges panels, therefore this ability requires special technical skills from the athletes. All teams, leaders of the world artistic swimming, from year to year, significantly complicate the competitive routines due to the greater number and complexity of acrobatic movements performed and the increase in the number of figure and elements hybrids with durable breath holding.